Erenumab aooe: a milestone for the preventive treatment of migraine - Singh, Gajendra Kumar; Kumar, Ratan; Chandra, Akash; Kumar, Ajay; Kumar, Upendra (International Journal of Research in Medical Sciences, 2020)
Migraine is a complex neurological condition, which can affect the whole body and can result in many symptoms as nausea, vomiting, photophobia (Increased sensitivity to light), phonobhobia (Increased sensitivity to sound) and osmophobia (Increased sensitivity to smell). Neurological symptoms that include visual disturbances such as blind spots, distorted vision, flashing lights or zigzag patterns. Other common symptoms includes- dizziness, vertigo, tingling sensations in the limbs, an inability to concentrate, confusion, difficulty in speaking, paralysis or loss of consciousness (in very rare cases). These symptoms, often called ‘aura’. Migraine attacks may differ in their frequency, duration and severity, although, normally they last between 4 and 72 hours, and most people are symptom-free between attacks. There are many drugs for the treatment of acute attack of migraine which can be divided into mild, moderate and severe attacks. In mild case NSAIDs like Paracetamol, Ibuprofen are prescribed. In moderate cases Anti-emetics like metoclopramide, domperidone can be prescribe with combinations of NSAIDs or triptans as sumatriptan. In case of severe cases triptans can be prescribed with ergot alkaloids and antiemetics. Following drugs are prescribed for the prophylaxis of migraine as sodium valproate, amitriptyline (Tricyclic antidepressant), propranolol and metoprolol (beta blockers). Erenumab-aooe is a calcitonin gene-related peptide receptor antagonist. It is specifically indicated for the preventative treatment of migraine in adults. Erenumab-aooe is supplied as an injection for subcutaneous use. The recommended dosage is 70 mg injected subcutaneously once monthly. Some patients may benefit from a dosage of 140 mg injected subcutaneously once monthly, which is administered as two consecutive subcutaneous injections of 70 mg each. Erenumab-aooe is a human monoclonal antibody that binds to the calcitonin gene-related peptide (CGRP) receptor and antagonizes CGRP receptor function.